Menelaah Sistem Hukum Pidana: Perbedaan antara KUHP Lama, KUHP Baru, dan Hukum Pidana di Luar KUHP. - Amelia, Fuji Nur Rizqi (Maliki Interdisciplinary Journal, 2024)
This article describes the systematic differences in criminal law between the Old Criminal Code, the New Criminal Code and the Extra-Criminal Criminal Code. The old Criminal Code, which was abolished in Dutch colonial law, has been used in Indonesia for decades, but is considered less relevant to the needs of modern society. For this reason, the new Criminal Code was designed with various updates aimed at updating and perfecting provisions that do not reflect current developments. Furthermore, there is criminal law outside criminal law which has an important role in filling legal weaknesses and criminal law provisions. This article provides a comparative analysis of this third aspect and considers the important changes brought about by the new criminal law and the role of extra-criminal law in the new and the role of extra-criminal law in the criminal punishment system in Indonesia.